Loss of molars in periodontally treated patients: results 10 years and more after active periodontal therapy - Dannewitz, Bettina; Zeidler, Anna-Kristina; Hüsing, Johannes; Saure, Daniel; Pfefferle, Thorsten; Eickholz, Peter; Pretzl, Bernadette (Journal of clinical periodontology, 2016)
Aim To identify risk factors for loss of molars during supportive periodontal therapy (SPT). Materials and Methods A total of 136 subjects with 1015 molars at baseline were examined retrospectively. The association of risk factors with loss of molars was assessed using a multilevel Cox regression analysis. Furcation involvement (FI) was assessed clinically at start of periodontal therapy and assigned according to Hamp et al. (1975). Results Fifty molars were extracted during active periodontal therapy (APT) and 154 molars over the average SPT period of 13.2 ± 2.8 years. FI degree III (HR 4.68, p < 0.001), baseline bone loss (BL) > 60% (HR 3.74, p = 0.009), residual mean probing pocket depth (PPD, HR 1.43, p = 0.027), and endodontic treatment (HR 2.98, p < 0.001) were identified as relevant tooth-related factors for loss of molars during SPT. However, mean survival time for molars with FI III or BL > 60% were 11.8 and 14.4 years, respectively. Among the patient data, age (HR 1.57, p = 0.01), female gender (HR 1.99, p = 0.035), smoking (HR 1.97, p = 0.034), and diabetes mellitus (HR 5.25, p = 0.021) were significant predictors for loss of molars. Conclusion Overall, periodontal therapy results in a good prognosis of molars. Degree III FI, progressive BL, endodontic treatment, residual PPD, age, female gender, smoking, and diabetes mellitus strongly influence the prognosis for molars after APT.
First published: 10 December 2015
Gesehen am 06.05.2020